2007
DOI: 10.1158/1078-0432.ccr-07-0671
|View full text |Cite
|
Sign up to set email alerts
|

DNA Replication Licensing Factors and Aurora Kinases are Linked to Aneuploidy and Clinical Outcome in Epithelial Ovarian Carcinoma

Abstract: Purpose: DNA replication licensing factors and Aurora kinases play critical roles in maintaining genomic integrity. We used multiparameter analyses of these cell cycle regulatory proteins to investigate their role in the progression of epithelial ovarian carcinoma (EOC). Experimental Design: In a cohort of 143 patients, we linked the protein expression profiles of the proliferation marker Ki67, the replication licensing factors Mcm2 and geminin, and the Aurora A and B kinases to tumor DNA ploidy status and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
60
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 45 publications
11
60
2
Order By: Relevance
“…Moreover, Mcm2-7 expression levels are powerful prognostic indicators in diverse tumour types, including cancers of the lung, breast, kidney, bladder, prostate and ovary [71][72][73][74][75][76][77]. This finding is consistent with large-scale meta-analysis of cancer microarray data, which identified up-regulation of the MCM2-6 genes as a component of poor prognostic signatures [78].…”
Section: Dna Replication Licensing and Cancersupporting
confidence: 71%
See 2 more Smart Citations
“…Moreover, Mcm2-7 expression levels are powerful prognostic indicators in diverse tumour types, including cancers of the lung, breast, kidney, bladder, prostate and ovary [71][72][73][74][75][76][77]. This finding is consistent with large-scale meta-analysis of cancer microarray data, which identified up-regulation of the MCM2-6 genes as a component of poor prognostic signatures [78].…”
Section: Dna Replication Licensing and Cancersupporting
confidence: 71%
“…As discussed above, expression of the Mcm2-7 proteins allows tumour cells engaged in the cell division cycle to be clearly distinguished from cells residing in out-of-cycle states. Geminin, which prevents relicensing of replication origins after the initiation of DNA synthesis, is only present in cells progressing through S, G 2 and M phases, as are the mitotic engine kinases Plk1, Aurora A and Aurora B [74,107,108]. These three kinases control most mitotic events, including centrosome maturation and separation, chromosome orientation and segregation [8].…”
Section: Geminin Mitotic Kinases and Phosphohistone H3 Can Be Used Tmentioning
confidence: 99%
See 1 more Smart Citation
“…After DNA replication is initiated during the cell cycle, Geminin inhibits re-uploading of the MCM proteins onto chromatin, thus preventing DNA re-replication in the same cell cycle (13). It has been confirmed that these proteins are useful biomakers that reflect the proliferative activity of the tumor cells and predict the survival of patients Multiparameter analysis using cell cycle biomarkers for small-size lung adenocarcinoma : Prognostic implications TOMOHIRO HARUKI 1,2 , KOHEI SHOMORI 1 , TATSUSHI SHIOMI 1 , YUJI TANIGUCHI 2 , HIROSHIGE NAKAMURA 2 and HISAO ITO 1 1 with various types of cancer (5)(6)(7)(8)(9)(10)(11)(14)(15)(16)(17)(18). Aurora A, known as a member of the serine/threonine kinase family, controls a subset of critical mitotic events including centrosome maturation and separation, as well as chromosome orientation and segregation (19).…”
Section: Introductionmentioning
confidence: 99%
“…However, these have not actually contributed to improving the prognosis of patients with early-stage NSCLC. Although almost all of these previous studies described the prognostic significance of a single biomarker, recent investigations have suggested that prognostic prediction is more reliable when multiparameter analysis with several biomarkers is performed than with analysis with a single one (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%